The Development Assessment Instruments of Higher Order Thinking Skills on Economic Subject - Kurniawan, Riza Yonisa; Lestari, Dian (Dinamika Pendidikan, 2019)
This research aims to develop Higher Order Thinking Skills (HOTS) based assessment instruments on economic subjects especially in Basic Competencies 3.4 price and inflation index. This study adopts the development model of Borg Gall which is limited to five stages of development, namely, data collection, product design, product testing, product analysis and final product revision. This research was conducted on 33 students of Social Eleven One class at Senior High School 1 Cerme. This assessment instrument produces 15 multiple choice test and has been tested twice. This study shows the results that in the first and second trials the overall validity value of the problem is greater than r table which is 0.344 and the reliability value is 0.786 and 0.763. This shows that the assessment instrument is valid and reliable. While the test for the quantity of items consists level difficulty of the question, differentiating question and effectivity of distractor that meet the quality criteria of HOTS-based questions. Based on the results of the trial it was found that there were 7 students who were included in the "less" category. Overall, the average student has a high level of thinking ability that requires sufficient categories. So, the efforts to support the learning process continue to be needed which is useful for improving higher order thinking skills in students.